Pengenalan Warna untuk Menciptakan Suasana pada Ruang Interior - siti indah lestari; Ramadhani, Ivo; Shiddiqi, M. Mu’ammar (Publikasi Pengabdian Masyarakat, 2024)
The community service activity entitled "Introducing Color to Create an Atmosphere in Interior Spaces" aims to increase the understanding and skills of vocational school students in using color to create the desired atmosphere in interior design. This activity involves theory sessions, practical workshops, and design projects designed to provide basic knowledge of color psychology and its application in the context of interior spaces. During the activity, students learned about various important aspects such as selecting color palettes, optimal space arrangement, and appropriate lighting to support interior design concepts. Through presentations and discussion sessions, they also improve their communication skills and receive constructive feedback from their instructors and peers. The results of the activity showed a significant increase in students' understanding and ability to apply color concepts in interior design. They succeeded in producing design projects that demonstrated creativity and the correct application of theory. Factors supporting the success of this activity include student enthusiasm, support from the school, and the quality of the materials and instructors. However, several obstacles such as limited time and practical tools are challenges that need to be overcome in the future. Suggestions for improvement include increasing the duration of activities, using more advanced design technology, and collaborating with professionals in the field of interior design. Overall, this activity makes a positive contribution to interior design education for vocational school students, equipping them with practical knowledge and skills that can be applied in real projects in the future.